The Methodology of Development for Learning Implementation Planning in the Industrial Era 4.0 - Arif Wahyudi (Tarbiyah Departement collaboration with AMCA, 2020)
learning is a plan that describes the procedures and management of learning to achieve one basic competency set out in the content standard and outlined in the syllabus. Therefore, this must be done seriously and not just to fulfill academic administrative requirements or just to please the supervisor. Since learning planning is an important step towards learning and achieving learning goals, it needs to be well prepared. amidst the demands of the times that continue to evolve and change as the industry era 4.0 today. Where teachers and educational institutions must really prepare the needs of skills and other expertise to improve the quality of the competence of students, and to determine it certainly requires a strategy. What is that strategy? Finesse is a way of working or doing things carefully / thoroughly.